Associations of air pollution with all-cause dementia, Alzheimer’s disease, and vascular dementia: a prospective cohort study based on 437,932 participants from the UK biobank - Yuan, Shiqi; Huang, Xiaxuan; Zhang, Luming; Ling, Yitong; Tan, Shanyuan; Peng, Min; Xu, Anding; Lyu, Jun (Frontiers in Neuroscience, 2023)
Objective: To prospectively assess whether air pollution, including PM2.5, PM10, and NOx, is associated with the risk of all-cause dementia, Alzheimer's disease (AD), and vascular dementia, and to investigate the potential relationship between air pollution and genetic susceptibility in the development of AD. Methods and Results: Our study included 437,932 participants from the UK Biobank with a median follow-up period of over 10 years. Using a Cox proportional hazards model, we found that participants exposed to PM2.5 levels of ≥10 μg/m3 had a higher risk of developing all-cause dementia (HR = 1.1; 95% CI: 1.05-1.28; p < 0.05) compared to the group exposed to PM2.5 levels of <10 μg/m3. However, there was no significant association between PM10 levels of ≥15 μg/m3 and the risk of all-cause dementia, AD, or vascular dementia when compared to the group exposed to PM10 levels of < 15 μg/m3. On the other hand, participants exposed to NOx levels of ≥ 50 μg/m3 had a significantly higher risk of all-cause dementia (HR = 1.14; 95% CI: 1.02-1.26; p < 0.05) and AD (HR = 1.26; 95% CI: 1.08-1.48; p < 0.05) compared to the group exposed to NOx levels of <50 μg/m3. Furthermore, we examined the combined effect of air pollution (PM2.5, PM10, and NOx) and Alzheimer's disease genetic risk score (AD-GRS) on the development of AD using a Cox proportional hazards model. Among participants with a high AD-GRS, those exposed to NOx levels of ≥50 μg/m3 had a significantly higher risk of AD compared to those in the group exposed to NOx levels of <50 μg/m3 (HR = 1.36; 95% CI: 1.03-1.18; p < 0.05). Regardless of air pollutant levels (PM2.5, PM10, or NOx), participants with a high AD-GRS had a significantly increased risk of developing AD. Conclusion: Our findings indicate that individuals living in areas with PM2.5 levels of ≥10 μg/m3 or NOx levels of ≥50 μg/m3 are at a higher risk of developing all-cause dementia. Moreover, individuals with a high AD-GRS demonstrated an increased risk of developing AD, particularly in the presence of NOx≥50 μg/m3.